Les recompositions territoriales de l’action publique à l’aune de la proximité - Catherine Carré; Eleni Chouli; José Frédéric Deroubaix (Développement Durable et Territoires)
Urban drainage is nowadays a good example in order to consider the issue of proximity in environmental and local development public policies. Usual drainage systems have proved to be not sufficient and excessively expensive. More and more alternative solutions are experimented and implemented in Northern American and European cities. These experiences are based on source control and sustainable urban drainage solutions (SUDS). SUDS require many changes, not only in the institutions taking part in urban drainage policy, but more generally in organisations involved in the construction of the city. Source control implies a switch from a sector-related and technical management to a contextual water management, involving a wide range of stakeholders, interacting in order to create an optimum living environment. Proximity is here used as a category of analysis in order to understand the on-going changes; proximity is than used as a way to assess the new drainage systems; finally we focus on existing possibilities to generalise source control taking into consideration that SUDS are always related to a local context. There is no doubt that decentralised urban drainage has generated new forms of public action; still SUDS development is always limited because of institutional and professional obstacles. There is no strong and common urban drainage policy referential that will lead all concerned stake-holders to cooperate in order to elaborate the most sustainable source control device. Most of the time, the success of the project depends on a specific political will. However, a growing number of hybrid networks, involving searchers and urban developers, are favouring local source control “cultures”.